(untitled) (World Bulletin of Social Sciences, 2024)
The article analyses the key stages in the development of modernization theory and its critiques, with a view to highlighting the shift from universal models to more culturally sensitive approaches. The article discusses political and social transformations in Arab monarchies, including reforms in institutional structures and the efforts of ruling elites to stabilise and modernize governance systems.